An evaluation of financial and non-financial environmental disclosures of ten publicly-listed mining companies in the Philippines - Aquino, Nimpha M. (Animo Repository, 2009)
This study determined the environmental disclosure practices of 10 mining companies in the Philippines by examining the nature and extent of disclosures in the financial and non-financial sections of their 2006 corporate annual reports. It was found out that there was no uniformity in the environmental disclosures of the 10 mining companies. It was also discovered that there was no existing environmental reporting standards as far as environmental disclosure is concerned. The study provided recommendations to the standard-setting council to improve the firms' environmental disclosure compliance with a discussion regarding the benefits these recommendations might offer. © 2009 De La Salle University, Manila, Philippines.